Effect of two different pre‐anaesthetic omeprazole protocols on gastroesophageal reflux incidence and pH in dogs. (26th March 2021) - Lotti, F.; Twedt, D.; Warrit, K.; Bryan, S.; Vaca, C.; Krause, L.; Fukushima, K.; Boscan, P.
Abstract : Objectives: Gastroesophageal reflux can occur during anaesthesia and may lead to esophagitis and occasionally oesophageal stricture formation. The aim of the study is to assess two omeprazole protocols on gastroesophageal reflux incidence and pH in anaesthetised dogs. Materials and Methods: Fifty‐five dogs undergoing elective ovariectomy were randomly assigned to: omeprazole single dose 1 mg/kg orally the evening before anaesthesia (20 dogs), omeprazole two doses 1 mg/kg orally the evening and 3 hours before anaesthesia (15 dogs), and control group that did not receive omeprazole (20 dogs). An oesophageal impedance/pH probe was used to measure gastroesophageal reflux incidence and pH during anaesthesia. Results: Gastroesophageal reflux was observed in 55% (11/20) of control dogs, 55% (11/20) of dogs receiving omeprazole once and 47% (7/15) of dogs receiving omeprazole twice. The incidence was not statistically significant different between groups. Gastroesophageal reflux pH (mean ± sd) was higher in dogs receiving omeprazole twice (6.3 ± 1.5), when compared to either control dogs (3.8 ± 1.1) or dogs receiving omeprazole once (4.1 ± 1.5). Strongly acidic reflux (pH < 4) was observed in 7% (1/15) of dogs receiving omeprazole twice versus 55% (11/20) and 35% (7/20) of control dogs and dogs receiving omeprazole once, respectively. Clinical Significance: Omeprazole administered the evening and 3 hours before anaesthesia increased gastroesophageal reflux pH and decreased the incidence of strongly acidic reflux in dogs. A single dose of omeprazole given the evening before anaesthesia had no effect on reflux pH.